An Investigation of How Hotel Image, Hotel Service Quality, Guest Loyalty, And Guest Experience Influence Luxury Hotel Guest Revisit Intention in Thailand - Sornsaruht, Puris (Journal of Ecohumanism, 2024)
This study examines the factors influencing the likelihood of luxury hotel guests returning for future visits. Drawing from existing literature, the author identified five underlying factors and 18 observable factors, leading to the formulation of nine conceptual hypotheses. The sample consisted of 317 guests from ten 5-star luxury hotels in Thailand. Utilizing structural equation modeling (SEM) with LISREL 9.10, it was determined that all variables in the model positively impacted the intention of luxury hotel guests to revisit, explaining 81% of the variance collectively (R2). Among these factors, hotel image emerged as the most significant predictor, followed by hotel service quality, guest loyalty, and guest experience. Notably, it was observed that there were strong connections between guest experience and service quality, as well as hotel image and service quality. Additionally, eight out of nine hypotheses received empirical support. This study underscores the importance of luxury hotels fostering a workforce aligned with the brand’s values, as staff play a pivotal role in influencing guest revisit intentions. These findings hold particular relevance as the tourism and hospitality industry navigates the post-COVID-19 recovery phase.